Clinical study of post partum haemorrhage from a teaching hospital in Maharashtra, India - Tasneem, Fasiha; Sirsam, Shyam; Shanbhag, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study the cases of postpartum haemorrhage, their causes and management in a tertiary care centre. Methods: A retrospective study of cases of postpartum haemorrhage for a period of 3yrs was conducted in Dept. of OBGY at a rural tertiary care center and teaching hospital in Maharashtra. The major causes, management modalities, morbidity and mortality associated with it were discussed. Results: Out of 37515 deliveries over the period of 3 years (2014-2016), there were 1333 cases of PPH out of which accounted for a prevalence of 3.55%. Study showed that 86% of cases were due to atonic PPH, 9.9% due to traumatic PPH, and 0.97% were due to both atonic and traumatic PPH. 2.7% of cases were due to retained placenta, 0.07% were due to bleeding diathesis. Conclusions: In an era with availability of excellent uterotonics and active management of 3rd stage of labour even today postpartum haemorrhage stands first as the cause of maternal morbidity and mortality. Even though with excellent medical and surgical interventions, maternal mortality due to PPH has been significantly reduced, the field still needs extensive research and new modalities to prevent and manage post-partum haemorrhage.